The new fourth branch : institutions for protecting constitutional democracy / Mark Tushnet, Harvard Law School. - Tushnet, Mark V., 1945- (Comparative constitutional law and policy., 2021)
Twenty-first-century constitutions now typically include a new 'fourth branch' of government, a group of institutions charged with protecting constitutional democracy, including electoral management bodies, anticorruption agencies, and ombuds offices. This book offers the first general theory of the fourth branch; in a world where governance is exercised through political parties, we cannot be confident that the traditional three branches are enough to preserve constitutional democracy. The fourth branch institutions can, by concentrating within themselves distinctive forms of expertise, deploy that expertise more effectively than the traditional branches are capable of doing. However, several case studies of anticorruption efforts, electoral management bodies, and audit bureaus show that the fourth branch institutions do not always succeed in protecting constitutional democracy, and indeed sometimes undermine it. The book concludes with some cautionary notes about placing too much hope in these - or, indeed, in any - institutions as the guarantors of constitutional democracy.